Ascertainment of Dementia Cases in the Spanish European Prospective Investigation into Cancer and Nutrition-Murcia Cohort (2019)
ABSTRACT: Background: Cohort studies generally focus on a particular disease, although they offer the possibility of evaluating different outcomes with minimal additional investment. The objective of this study was to describe the methodology used to assess dementia in the European Prospective Investigation into Cancer and Nutrition (EPIC)-Murcia study. Methods: The EPIC-Murcia cohort consists of 8,515 healthy participants (68% women, aged 30–70 years), recruited between 1992 and 1996 and followed up for over 20 years. Incident cases were ascertained by a 2-step protocol: a record linkage with health databases to identify potential events and a review of medical records of potential cases to validate incident cases. Results: Overall, 1,202 potential cases were identified, and 275 dementia cases were validated. Medical reports were the source of information in 243 cases, with complete neurological information in 227, and a high degree of certainty of the diagnosis in 229 cases. P70 (dementia code) and/or antidementia drugs and/or ICD codes identified 259 cases (sensitivity: 94.2%, 95% CI 90.7–96.6; specificity: 98.1%, 95% CI 97.8–98.4). Conclusion: Ascertainment of incident dementia in the EPIC-Murcia cohort study was feasible using information from medical records. This systematic 2-step validation protocol is proposed as a feasible way to ascertain dementia in cohort studies originally designed for other endpoints.